EMG controlled bionic robotic arm using artificial intelligence and machine learning - Rupom, Farhan Fuad; Johan, Gazi Musa Al; Jannat, Shafaitul; Tamanna, Farjana Ferdousi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.